The Fourth Estate Unbound: Examining Press Law and Ethics in the Digital Age in Indonesia - Maharani, Elita (Indonesia Media Law Review, 2024)
In Indonesia, the digital age has transformed the media landscape, ushering in new opportunities and challenges for press freedom, law, and ethics. This paper investigates the evolving role of the press in Indonesia's digital era, with a specific focus on the legal and ethical dimensions. It delves into the implications of online platforms and social media on news dissemination, exploring the regulatory frameworks governing journalism and the ethical dilemmas faced by journalists. Additionally, it examines the impact of digital technology on media ownership, censorship, and the proliferation of misinformation. Through case studies and scholarly research, the paper seeks to provide insights into how Indonesian media can navigate these complexities while upholding press freedom and ethical standards. Key areas of analysis include the historical context of press freedom, integrity in online news reporting, challenges to traditional media outlets, strategies for combating misinformation, and the legal implications of digital journalism. Ultimately, the paper aims to contribute to a deeper understanding of how Indonesia's media can adapt and thrive in the digital age while maintaining their essential role as guardians of democracy and public discourse.